THE ACTUALIZATION AND RECONCILIATION OF ISLAMIC-BASED DEMOCRACY: A PERSPECTIVE FROM THE BOOK AL-TIBYĀN FĪ AL-NAHY’ĀN MUQATĀ’AH AL-ARHAM WA AL-AQĀRIB WA AL-IKHWĀN BY HADRATUSSYAIKH KH. M. HASYIM ASY’ARI - Amalia; Khoirotul Idawati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Reviving or campaigning again regarding the values ​​of peace and reconciliation efforts in maintaining togetherness, harmony, and peace of the Indonesian nation, which recently some leaders have actually become pioneers of division. The thoughts of Hadratussyaikh KH. M. Hasyim Asy'ari regarding the value of reconciliation in the Book of al-Tibyan fi al-Nahy'an Muqatha'ah al-Arham wa al-Aqarib wa al-Ikhwan are something interesting to study in answering this problem. The reason is, this book will be a solution to several phenomena that occur amidst the turmoil and turmoil of hostility and competition for life between Indonesian and even world communities. This study uses a library research approach using descriptive data analysis and content analysis, with the aim of understanding the phenomena related to what is the problem in the study. Based on the results of the study, it can be concluded that the actualization and reconciliation of democracy based on Islam in the perspective of the Book of Al-Tibyan by Hadratussyaikh KH. M. Hasyim Asy'ari's approach begins with the practice of social gatherings, which serve as a means of cultivating empathy among people. In the context of the actualization and reconciliation of Islamic-based democracy, a nation will be strong and great if the democracy it builds is also sound and strong, and it also makes individuals and Indonesians aware that direct and indirect communication is a tool for unifying paradigms that every citizen must possess. This way, humans can become beings who aim to draw closer to Allah SWT and achieve happiness in this world and the hereafter.